1976
DOI: 10.1530/jrf.0.0480001
|View full text |Cite
|
Sign up to set email alerts
|

Rat alpha-fetoprotein: isolation, radioimmunoassay and fetal-maternal distribution during pregnancy

Abstract: Summary. A method is described for the isolation of mg quantities of two forms of rat alpha-fetoprotein (AFP) from amniotic fluid by preparative disc-gel column electrophoresis using a continuous elution system. AFP isolated by this method is suitable for use as an antigen, can be labelled for use in a radioimmunoassay and serves as a reference standard. The characteristics of a new antiserum to AFP are also described.The protocol for a radioimmunoassay is outlined which permits the measurement of AFP in sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
1

Year Published

1976
1976
1988
1988

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 13 publications
1
24
1
1
Order By: Relevance
“…The AFP level in maternal plasma of animals in Group 2 after partial occlusion of the uterine arteries remained only slightly elevated until 48 hr after surgery when it more closely paralleled the level observed in sham-operated control rats. Plasma AFP in hysterectomized rats (Group 3) decreased steadily with a half-life of approximately 27 hr between 24 and 72 hr after surgery, and the pattern of maternal plasma AFP levels during pregnancy in the sham-operated controls (Group 4) was similar to that previously reported for normal pregnant rats (Lai et al, 1976).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The AFP level in maternal plasma of animals in Group 2 after partial occlusion of the uterine arteries remained only slightly elevated until 48 hr after surgery when it more closely paralleled the level observed in sham-operated control rats. Plasma AFP in hysterectomized rats (Group 3) decreased steadily with a half-life of approximately 27 hr between 24 and 72 hr after surgery, and the pattern of maternal plasma AFP levels during pregnancy in the sham-operated controls (Group 4) was similar to that previously reported for normal pregnant rats (Lai et al, 1976).…”
Section: Resultssupporting
confidence: 83%
“…Plasma (10-20 µ ) was stored at -20°C in 1 ml 005 M-phosphate buffer (pH 7-5) containing 0-5% bovine serum albumin. Radioimmunoassay of plasma AFP was as previously described (Lai et al, 1976). The rats were asphyxiated with carbon dioxide on Day 20 ofgestation and each live fetus and placenta was removed and weighed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one protein associated with fetal development and studied in detail in several mammalian species including the cow has been alpha,-fetoprotein (Branch, 1972;Lai, Forrester, Hay, Hancock & Lorscheider, 1976; …”
Section: Introductionmentioning
confidence: 99%
“…It is interest ing that Alpert et al [13] have indicated that they believed the immunosuppressive effects of human fetal and tumor serum were due to factors other than AFP since the purified protein had no activity. However, the plasma of pregnant rats, which at term con tains about 4.3 mg% AFP and which is ap proximately 100 times more than is present in human plasma at a similar stage of preg nancy [27,28], did not suppress the develop ment of EAE. The amount of rat AFP present in the 600 pi of the pregnant rat plasma administered every 2nd day would have been approximately 25 pg.…”
Section: Discussionmentioning
confidence: 80%